MULTICULTURAL EDUCATION BASED ON RELIGION IN INDONESIA AND AUSTRALIA - Na’imah Na’imah (International Conference on Social and Islamic Studies, 2022)
Religious multicultural education contains various characteristics to empower people's peace and freedom in their multicultural life both in Indonesia and  Australia. The multicultural form of religion reflects the culture of its people, lifestyle, diet, including the language used for worship and communication. This study is based on the phenomenon in Yogyakarta, Indonesia and Newcastle, Australia which in fact these two parts of the country reflect the big picture of other countries. The purpose of this study is to show the characteristics of the culture of the people in two unique countries, which are different from previous studies. The research was conducted with a descriptive qualitative approach, which relies on qualitative data collected through observation and documentation, which is then analyzed, reduced, verified, until meaningful research results are found. The results showed 3 main things, namely (1) the form of religious multicultural education (Islam, Christianity, Catholicism, Hinduism, Buddhism, Confucianism, and religious beliefs)  Yogyakarta, Indonesia in the first semester of 2021; (2) The form of multicultural religious education for the people of Newcastle, Australia, (Buddism; Christianity nfd; Christianity, nfd Western Catholic; Greek Orthodox; Macedonian Orthodox; Presbyterian. Chrch' Pentecostal, nfd; Hinduism; Islam; ; Inadequately described; Not Stated; No Religion; (3) The characteristics between these countries are; continue to understand the language, worship, dress, diet, and lifestyle with culture